2008
DOI: 10.1111/j.1475-097x.2008.00818.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure and heart rate variability analysis of orthostatic challenge in normal human pregnancies

Abstract: The aim of the present study was to evaluate pregnancy-related changes in autonomic regulatory functions in healthy subjects. We studied cardiovascular autonomic responses to head-up tilt (HUT) in 28 pregnant women during the third trimester of pregnancy and 3 months after parturition. The maternal ECG and non-invasive beat-to-beat blood pressure were recorded in the horizontal position (left-lateral position) and during HUT in the upright position. Stroke volume was assessed from blood pressure signal by usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 28 publications
4
17
0
1
Order By: Relevance
“…However, in agreement to earlier observations [17], [46], respiratory frequency remained unaltered throughout pregnancy, apart from increased tidal volume leading to an increased minute volume. The analysis of BRS using the sequence method provides an index of autonomic nervous activity on RRI.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, in agreement to earlier observations [17], [46], respiratory frequency remained unaltered throughout pregnancy, apart from increased tidal volume leading to an increased minute volume. The analysis of BRS using the sequence method provides an index of autonomic nervous activity on RRI.…”
Section: Discussionsupporting
confidence: 92%
“…Our analysis suggests that the increase of HR throughout normal pregnancy is mainly driven by decreased parasympathetic activity, which confirms earlier observations [46]. Ekholm et al found decreased parasympathetic responsiveness in early and mid-pregnancy with some restoration in the third trimester, along with diminished HRV, suggesting decreased parasympathetic and/or increased sympathetic nervous system tone [44], [47].…”
Section: Discussionsupporting
confidence: 91%
“…Similar conclusions were obtained by considering the changes in LF/HF ratio. Signifi cant reduction in RMSSD, NN50 count, pNN50% and HF (ms Heiskanen et al's., [15] study showed that in normal pregnancy, the increment of the heart rate could be partially associated with the inhibition of resting parasympathetic activity connected with an increment of the sympathetic modulation but during the 3 rd third trimester of pregnancy there could be a parasympathetic deactivation instead of an increment of the sympathetic activity (under unstimulated conditions) even when the head-up tilt test induce changes in the parasympathetic activity and the sympathovagal balance.…”
Section: Discussionmentioning
confidence: 91%
“…This effect is very prominent at the level of the hepatic veins (HV), in which the first‐trimester triphasic venous pulse wave shifts to a completely flat pattern during the late second and third trimesters. These changes take place alongside important physiological gestational adaptations of the maternal body, among which are an increase in venous return and intravascular volume by altered renal function (vascular perfusion and drainage, glomerular and tubular function, hormonal production and response), a coordinated balanced change in baroreflex sensitivity of the heart and vasculature and raised external venous compression by an increase in intra‐abdominal pressure. The latter also contributes to the development of varicose veins and physiological malleolar edema during the course of pregnancy.…”
Section: Normal Gestational Changes In Venous Hemodynamics and Plasmamentioning
confidence: 99%